2002
DOI: 10.1161/01.cir.0000033116.22237.f9
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration That C-Reactive Protein Decreases eNOS Expression and Bioactivity in Human Aortic Endothelial Cells

Abstract: Background-C-reactive protein (CRP), the prototypic marker of inflammation, has been shown to be an independent predictor of cardiovascular events. Endothelial nitric oxide synthase (eNOS) deficiency is a pivotal event in atherogenesis. Methods and Results-We tested the effect of CRP on eNOS expression and bioactivity in cultured human aortic endothelial cells (HAECs). CRP decreased eNOS mRNA, protein abundance, and enzyme activity in HAECs. Furthermore, eNOS bioactivity assayed by cyclic GMP levels was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
497
3
34

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 774 publications
(558 citation statements)
references
References 27 publications
17
497
3
34
Order By: Relevance
“…These findings provide insight into CNS immune mechanism associated with APOE alleles and build upon a growing body of literature showing that APOE may moderate aspects of immunity [Laskowitz, Lee, et al 2000] [Tenger, Zhou 2003]. One interesting connection between our study and those findings is the fact that CRP has been shown to inhibit NO synthase [Venugopal, Devaraj, et al 2002]. It is possible that through APOE4 effects on CRP, individuals with lower CRP are at increased risk of higher NO production in the CNS and greater risk of AD.…”
Section: Discussionsupporting
confidence: 78%
“…These findings provide insight into CNS immune mechanism associated with APOE alleles and build upon a growing body of literature showing that APOE may moderate aspects of immunity [Laskowitz, Lee, et al 2000] [Tenger, Zhou 2003]. One interesting connection between our study and those findings is the fact that CRP has been shown to inhibit NO synthase [Venugopal, Devaraj, et al 2002]. It is possible that through APOE4 effects on CRP, individuals with lower CRP are at increased risk of higher NO production in the CNS and greater risk of AD.…”
Section: Discussionsupporting
confidence: 78%
“…Yet, as most of the experiments were in tissue culture with cause-effect exhibited following the use of commercial CRP preparations concern has been raised for spurious effects of contaminants. When impurities, in particular the preservative sodium azide and the contaminant endotoxin, are removed from commercial CRP preparations the putative direct endothelial activity is questioned [23][24][25][26][27][28]. Transgenic animals that express human CRP, or mice that express rabbit CRP [20], can be used to resolve the issue of this suspected spurious artifactual results.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies, both in the injured artery and the distant lung tissue, indicate that CRP exerts an opposite effect, with suppression of p38 MAPK. These contradictory findings may result from the in vitro methodology which exposes the study to the risk of contamination with preservatives and endotoxin [23][24][25][26][27][28]. Another explanation is a possible differential effect of CRP on blood mononuclear cells and arterial and alveolar cells.…”
Section: Discussionmentioning
confidence: 99%
“…HAECs (Clonetics, San Diego, CA) were cultured as described previously (12) and were used within five passages for all experiments. CRP was purified from human pleural or ascites fluid by the method of Du Clos, Zlock, and Marnell (13).…”
Section: Cell Culture and Human Crp Purificationmentioning
confidence: 99%